PERKEMBANGAN ASAS TUGAS PEMBANTUAN DI INDONESIA - Rauf, Rahyunir (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2018)
In the long journey of development of a government increasingly multiply and enrich the understanding of the government itself, so that the concepts of government can be viewed from various angles and aspects that can further clarify the notion of the concept of government itself, one of which is the concept of the principle of governance. The existence of a Local Government in the system of government is an integral part of a system of state government or national government, even the concept and theoretical existence of local government is much earlier than the existence of elements of central government or state government. The principle of "Medebewin" as a relic of the Indies government system, at the beginning of the revolution, precisely in 1948, was called "uncompleted surrender", to overcome the principle of full-fledged decentralization. The difference with the principle of decentralization is that the "medebewind" governmental affairs are only handed over the task of execution alone, excluding the authority that determines the policies, the financing, and the execution workers. One of the principles of local governance that has been applied in Indonesia in the history of local governance is the Assistance Task Principle, apart from the principles of decentralization and deconcentration. The principle of the implementation of regional government consists of the principle of decentralization, the principle of deconcentration and the principle of co-administration. In Dutch legislation, between co-administration and medebewin are divided into two, namely mechanical medebewind or more detailed andfacultative medebewind or which provide wider freedom to determine the wisdom of the medebewind ". Definition of assistance task is; assignment with an obligation to account for its execution to the assignee. In its implementation the task of assistance has its own development and dynamics in accordance with the Law on Regional Government which regulates it.